Modified Graded Repair of Cerebrospinal Fluid Leaks in Endoscopic Endonasal Transsphenoidal Surgery - Park, Jae-Hyun; Choi, Jai Ho; Kim, Young-Il; Kim, Sung Won; Hong, Yong-Kil (Journal of Korean Neurosurgical Society, 2015)
Complete sellar floor reconstruction is critical to avoid postoperative cerebrospinal fluid (CSF) leakage during transsphenoidal surgery. Recently, the pedicled nasoseptal flap has undergone many modifications and eventually proved to be valuable and efficient. However, using these nasoseptal flaps in all patients who undergo transsphenoidal surgery, including those who had none or only minor CSF leakage, appears to be overly invasive and time-consuming. Patients undergoing endoscopic endonasal transsphenoidal tumor surgery within a 5 year-period were reviewed. Since 2009, we classified the intraoperative CSF leakage into grades from 0 to 3. Sellar floor reconstruction was tailored to each leak grade. We did not use any tissue grafts such as abdominal fat and did not include any procedures of CSF diversions such as lumbar drainage. Among 200 cases in 188 patients (147 pituitary adenoma and 41 other pathologies), intraoperative CSF leakage was observed in 27.4% of 197 cases : 14.7% Grade 1, 4.6% Grade 2a, 3.0% Grade 2b, and 5.1% Grade 3. Postoperative CSF leakage was observed in none of the cases. Septal bone buttress was used for Grade 1 to 3 leakages instead of any other foreign materials. Pedicled nasoseptal flap was used for Grades 2b and 3 leakages. Unused septal bones and nasoseptal flaps were repositioned. Modified classification of intraoperative CSF leaks and tailored repair technique in a multilayered fashion using an en-bloc harvested septal bone and vascularized nasoseptal flaps is an effective and reliable method for the prevention of postoperative CSF leaks.